A business model canvas for crowdfunding platform: case study of crowdfunding platforms in Malaysia - Muhammad Hakim Bin Nadir; Syaripah Ruzaini Syed Aris; Norjansalika Janom; Fauziah Ahmad; Noor Habibah Arshad; Nor Shahniza Kamal Bashah (Institute of Advanced Engineering and Science, 2020)
Crowdfunding allows entrepreneurs raise fund to help subsidizing their project. In other country, crowdfunding platform has become famous. In the contrary, it is yet to be trend in Malaysia. Financing using internet still irrelevant among Malaysian citizen. Without a proper guideline and strong crowdfunding platform based in Malaysia as a benchmark, it is hard to convince entrepreneurs and funders to consider crowdfunding as an option to fund a project. This research thus proposed business model canvas which can be applied by the crowdfunding platform organizations to manage their business and operation more efficiently. Case study method has been employed with two techniques of data collection: interview and document review. Two crowdfunding platforms based in Malaysia participated in the case study. The findings show that both crowdfunding platforms have fundamental business model elements that made of a solid foundation as a crowdfunding platform. These results offer insight into crowdfunding environment and how it links to another necessary part of business for it to function as a successful business. Nine building blocks fits well in the crowdfunding platform business model elements namely partner network, core competency, key resources, value proposition, customer relationship, distribution channel, customer segments, cost structure and revenue stream. Interestingly, the findings revealed another imperative element that should be part of the canvas: risk management.